Ability self-concept formation in elementary school: No dimensional comparison effects across time - Weidinger, Anne Franziska; Steinmayr, Ricarda; Spinath, Birgit (Developmental psychology, 2019)
In line with the reciprocal internal/external frame of reference model (RI/E model), it is well-established that secondary school students generate domain-specific ability self-concepts by comparing their own performance in a domain socially (i.e., with others’ performance in this domain) and dimensionally (i.e., with their own performance in other domains). However, developmental theories of ability conceptions suggest that the use of such performance comparisons to evaluate own abilities may differ by students’ developmental stage because of important developmental changes between early and late childhood. Yet, to our knowledge, no study has investigated dimensional comparison effects in elementary school longitudinally although this can provide valuable information on the formation of ability self-concepts. Thus, we tested whether longitudinal dimensional effects on changes in students’ ability self-concepts occur in the early school years. Ability self-concepts and grades in math and German of 542 German elementary school students were assessed seven times over 24 months from Grade 2 (M = 7.95 years of age, SD = 0.58) to Grade 4. Cross-sectional analyses showed some evidence for dimensional effects of students’ math grades on their German self-concepts, but not of students’ German grades on their math self-concepts. Longitudinal analyses with latent cross-lagged models revealed no evidence for longitudinal dimensional effects on changes in children’s ability self-concepts. Findings indicate that dimensional comparisons are not as important in ability self-concept formation in the first school years as they tend to be later on. Findings underline the importance of considering developmental differences to better understand ability self-concept formation. (PsycINFO Database Record (c) 2019 APA, all rights reserved)
Gesehen am 21.05.2019